Effect of heat treatment temperature on SN-0.7CU solders material on microstructure - Nabhan, Ismil (2007)
Soldering plays the most important role for joining technology in electronic industry.The conventional tin-lead solders have been used for a quite long time in electronic industries.However,since lead is a toxic element and harmful to individual health and environment,many researchers have proposed lead-free solder to protect individual health and environment as well.The objective of this study is to analyze the microstructure at the solder and base metal interface.This study investigates the interfacial reactions between Sn-0.7Cu solder material and copper substrate before and after aging at 100°C, 150°C and 200°C for 1 hour,3 hours and hours.Copper substrates are connected to each other by manual soldering.After soldering, the intermetallic compound formed at the interface is Cu6Sn5 intermetallic compound.The thickness of the intermetallic compound increases as the aging time and temperature increased. Intermetallic compound layer must be keep at sufficient thickness because excessive amount of intermetallic compound can generate defect and affect the solder joint reliability.